Effects of eliminating tension by means of epineural stitches: a comparative electrophysiological and histomorphometrical study using different suture techniques in an animal model - J Bustamante; M Socolovsky; R S Martins; J Emmerich; M G Pennini; N Lausada; L Domitrovic (Arquivos de Neuro-Psiquiatria)
Epineural stitches are a means to avoid tension in a nerve suture. We evaluate this technique, relative to interposed grafts and simple neurorraphy, in a rat model. METHOD: Twenty rats were allocated to four groups. For Group 1, sectioning of the sciatic nerve was performed, a segment 4 mm long discarded, and epineural suture with distal anchoring stitches were placed resulting in slight tension neurorraphy. For Group 2, a simple neurorraphy was performed. For Group 3, a 4 mm long graft was employed and Group 4 served as control. Ninety days after, reoperation, latency of motor action potentials recording and axonal counts were performed. Inter-group comparison was done by means of ANOVA and the non-parametric Kruskal-Wallis test. RESULTS: The mean motor latency for the simple suture (2.27±0.77 ms) was lower than for the other two surgical groups, but lower than among controls (1.69±0.56 ms). Similar values were founding in both group 1 (2.66±0.71 ms) and group 3 (2.64±0.6 ms). When fibers diameters were compared a significant difference was identified between groups 2 and 3 (p=0.048). CONCLUSION: Good results can be obtained when suturing a nerve employ with epineural anchoring stitches. However, more studies are needed before extrapolating results to human nerve sutures.